Rifting and recharge as triggers of the mixed basalt-rhyolite Halaraudur ignimbrite eruption (Krafla, Iceland) - Shane M. Rooyakkers; John Stix; Kim Berlo; Daniele Morgavi; Maurizio Petrelli; Monika K. Rusiecka; Simon J. Barker; Bruce L. A. Charlier; David A. Neave; Francesco P. Vetere; Diego Perugini (Contributions to Mineralogy and Petrology, 2022)
We present a petrologic study of the ca. 110 ka Halarauour eruption (7 +/- 6 km(3) magma), associated with collapse of Krafla caldera in northeast Iceland. Whole-rock compositions of juvenile Halarauour products span a continuous range between quartz tholeiite basalt (50.0 wt% SiO2, 5.0 wt% MgO; Mg# 42) and rhyolite (74.6 wt% SiO2). Linear correlations between all major elements are consistent with two-component mixing of sub-equal volumes of these end-member magmas, whereas correlations between trace elements are influenced by diffusive fractionation during chaotic mixing. Evolved compositions (andesite to rhyolite) and compositional heterogeneity are typical of early-erupted units, reflecting tapping of the upper, more silicic regions of a compositionally heterogeneous reservoir undergoing chaotic mixing. Later-erupted deposits are more compositionally homogeneous and grade smoothly upward from andesite to basalt, reflecting tapping of denser hybrid magma and uncontaminated basalt from lower in the chamber. All erupted products host < 1-2 modal% macro-crysts, implying storage at near-liquidus temperatures. Geobarometry and MELTS modeling suggest shallow storage pressures of similar to 200 MPa (similar to 8 km depth) for the quartz tholeiite. Plagioclase (An(60-76)) and augite (Mg# 68-75) macro-crysts crystallized from this basalt during shallow storage, while sparse glomerocrysts (plagioclase +/- augite +/- olivine +/- orthopyroxene) in late-erupted basaltic material are derived from disaggregated cumulate mush and include more primitive compositions. Occasional narrow sodic rims on plagioclase crystals from the quartz tholeiite record short periods of re-equilibration with hybrid magmas during mixing, constrained by experimental growth rates as at most two months and possibly as short as tens of hours. A second population of calcic plagioclase (cores An(83-91)) with adhering primitive basaltic glass selvages (Mg# 53-59) occurs sparsely in deposits of the first eruptive phase and is scarce or absent in ...